2006
DOI: 10.1210/jc.2006-0397
|View full text |Cite
|
Sign up to set email alerts
|

The Knudson’s Two-Hit Model and Timing of Somatic Mutation May Account for the Phenotypic Diversity of Focal Congenital Hyperinsulinism

Abstract: Background: Congenital hyperinsulinism (CHI) is associated with focal hyperplasia of endocrine tissue in 40 -65% of patients. Focal CHI is sporadic and is caused by a germline, paternally inherited, mutation of the SUR1 (ABCC8) or KIR6.2 (KCNJ11) genes (encoding subunits of the pancreatic ATP-dependent potassium channel) together with somatic maternal haploinsufficiency for 11p15.5. Plurifocal or large forms of focal CHI are a cause of apparent failure of surgery, and their underlying mechanism has not been th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 42 publications
1
28
0
Order By: Relevance
“…After resection of the accumulation in the uncinate process, the diffuse involvement of the remaining pancreas became apparent. There are only a few cases described so far that really showed two or more independent focal lesions within an otherwise normal pancreas (27,28,30). Most cases of "newly " detected focal lesions after surgery are probably either remaining adenomatosis after an incomplete resection or unevenly distributed hyperactivities within the intermediate form of CHI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…After resection of the accumulation in the uncinate process, the diffuse involvement of the remaining pancreas became apparent. There are only a few cases described so far that really showed two or more independent focal lesions within an otherwise normal pancreas (27,28,30). Most cases of "newly " detected focal lesions after surgery are probably either remaining adenomatosis after an incomplete resection or unevenly distributed hyperactivities within the intermediate form of CHI.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we take multiple frozen sections from the remaining pancreatic tissue as recommended by other groups (11,32,33). Furthermore, the rare but existing possibility of a second or third focus within the pancreas must be considered to be a possible reason for failure of surgery (27,30).…”
Section: Discussionmentioning
confidence: 99%
“…Despite undergoing the second surgery this patient was reported to be dependent on continuous gastrostomy feeds to maintain euglycemia [12] . Giurgea et al [47] reported that the size of the focal lesion is determined by the timing when the somatic loss of maternal allele occurs during the gestational age [47] . The earlier it occurs the larger the size of the focal lesion can be, as found in the 3 patient in this report.…”
Section: F-dopa-pet/ct In Chimentioning
confidence: 99%
“…The earlier it occurs the larger the size of the focal lesion can be, as found in the 3 patient in this report. Also it has been suggested that an unknown mechanism might play a role in different rate of tracer uptake in different regions of pancreas in large focal lesions [47] . Meintjes et al [26] recently evaluated and reported the accuracy of delineating the focal and diffuse CHI using 18 F fluoro-L-DOPA/CT and contrast enhanced CT.…”
Section: F-dopa-pet/ct In Chimentioning
confidence: 99%
“…Because of the difficulty to ensure normoglycemia by the conservative treatment modalities, the standard treatment for patients with early-onset CHI has in many centers been near-total (95%) pancreatectomy [4, 18, 35, 36]. However, it has now become apparent that 30–60% of neonatal-onset CHI is caused by the focal form of the disease [8, 9, 37, 38]. In most cases, only a tiny pancreatic lobulus of <1 cm is affected.…”
Section: Differential Therapymentioning
confidence: 99%